Development of learning module based on blended learning in network design lesson - Panyahuti Panyahuti; Kasman Rukun; Waskito Waskito (International Conferences on Educational, Social Sciences and Technology)
This research is written based on the learning difficulties during the internship activities. This research is to produce learning module for students who implement internship with Blended Learning model. Web-based or Android-based e-learning with the combined method of online manual learning can overcome these obstacles, because it can serve the students in large quantities, the time required is relatively short,it is flexible learning process, and teaching materials can be absorbed quite effectively. The purpose to know the validity of modules, the effectiveness, and effectiveness of the developed learning modules. The method used is a Research and Development (R & D) by using the FOUR D development model that are the definition, design, development, and deployment. The research design used for trial module is quasi experiment with time series model. The module made is valid by the material expert with the average of all eligibility is 80.38%, included in the "Excellent" category. The modular practicality analysis is 81.41%, included in the "Practical" category. Module effectiveness analysis, included in the "Good" category. From both data analysis results done, it can be stated that the module is effective in improving learning outcomes.